The Effect of Obesity and Flexibility Toward Women’s Body Fat in Productive Age at Larasati Gymnastic Semarang Member - Eva Faridah (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
Obesity is an body fat increase. Overweight is a relative body weight increase when compared to the standard. Overweight then became a term that represented "obesity" both clinically and epidemiologically. Flexibility is the effectiveness of a person in adjusting himself to all activities with stretching the body in a wide area of the joint. The design used in this study is a 2x2 factorial. It is explained about factorial experiments that what is measured is not only the influence of the main factor of each independent variable on the dependent variable, but also the influence of the interaction between the independent variables. The population in this study is the 50 members of Larasati gymnastics in Semarang, who in productive age women between 30-40 years.The number of samples is quite representative (representing) for the large population in this study. The sampling technique in this study was using purposive sampling, which is a sampling technique determined by giving equal opportunity to each member of the population as a sample, namely the number is adjusted to the member of the subject in each group, the experimental group of obesity type pear and apple type obesity control group. Based on the results of the research achieved, it turns out that women who have high flexibility have a large reduction in fat if they have the apple type of obesity. Women who have high flexibility with apple obesity type have a better decrease in body fat than women with low flexibility and have pear obesity type. Fcount = 6.962> Ftable = 3.11. The effectiveness that is applied to reduce body fat is influenced by the type of high flexibility and type of low flexibility of those women.